Studies on larvicidal potential of actinomycetes isolated from various regions of Chennai - Nandhini, S. Usha (Asian Journal of Pharmaceutics (AJP), 2020)
Background: Actinomycetes are organisms with characteristics common to both bacteria and fungi. It acts against Gram-positive bacteria and fungi. It is non-pathogenic. It is also able to produce different compounds such as anticancer, larvicidal compounds, pigments, and secondary metabolites. Objective: The objective of this study was to isolate and identify active actinomycetes from terrestrial soil sample for larvicidal activity. Methodology: The larvicidal crude compounds were extracted from the actinomycetes by solvent extraction method. The identification and characterization of active strain by using cultural characteristics and scanning electron microscopy image. The purified active larvicidal compounds were identified by using UV –spectrophotometry, Fourier transform infrared (FT-IR) and Gas chromatography–mass spectrometry (GC–MS) analysis. Results and Discussion: Active crude compound showed that LC50 value was found to be 62.5 µl. The identification of bioactive compound ranges from 254 nm to 265 nm was done by UV spectrum. FT-IR analysis was showed that functional groups such as alcohol, alkane, carboxylic acid, aromatics, alkene, and aliphatic amines were present, of which alkane group was predominant. GC–MS analysis report was showed that 1-Eicosanol has significant larvicidal potential of actinomycetes. Conclusion: The purpose of this study is to explore the larvicidal activity of natural microbial isolates of actinomycetes species which are isolated from soil against the life-threatening diseases caused by mosquitoes.